CBCT assessment of mandibular molar furcation following root canal retreatment using engine-driven instruments - Paulo Otávio Carmo SOUZA; Mike Reis BUENO; Brunno Santos de Freitas SILVA; Luiz Eduardo GREGORIS; Nádia do Lago COSTA; Carlos ESTRELA (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study employed e-Vol DXS cone beam computed tomography (CBCT) software to assess dentin remnants in the furcation area of mesial canals in mandibular molars during root canal retreatment (RCR). Four groups (Reciproc®, ProTaper Next®, Race Evo®, Protaper Gold®) were subjected to RCR, and CBCT images were captured before (T1) and after (T2) treatment. Measurements of remaining dentin thickness at 1 mm and 3 mm below the furcation were scrutinized. Results revealed no significant differences in mean thicknesses of mesiobuccal (MB) and mesiolingual (ML) canals at 1 mm and 3 mm from the furcation pre-treatment (T1). Post-treatment (T2) showed analogous findings, with no significant differences in mean thicknesses. However, disparities were found between MB and ML canals at both distances, both before and after retreatment. In essence, the evaluated instruments exhibited safety in RCR, implying that they are appropriate for use in critical areas of mandibular molars without inducing excessive wear. This study underscores the reliability of these instruments in navigating danger zones during RCR, and contributes valuable insights for dental practitioners who handle complex root canal scenarios in mandibular molars.